Analisis Kesalahan Morfologi Bahasa Indonesia dalam Karangan Narasi Peserta Didik Kelas V Sekolah Dasar - Aprilia Maharani Tunggal Putri; St Y Slamet; Jenny Indrastoeti Siti Poerwanti (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2023)
This aims of this study are to describe: (1) the form of affixation error, (2) the form of reduplication error, (3) the form of compounding error, (4) the cause of morphological error in narrative essays of fifth grade student in SD Negeri 1 Karangasem Surakarta. The research is a qualitative descriptive study with a sample of students’ narrative essays. The subject of the study is fifth grade student and the fifth grade teacher in SD Negeri 1 Karangasem. The object of this research is morphological error in students’ narrative essayas. Data collection using observation techniques, interviews, and documentation. The data validity test used triangulation techniques. Data analysis technique using Tarigan language error analysis. The results of this study showed that there were 147 affixation errors (82,13%), 31 of reduplication errors (17,31%), and 1 compounding error (0,56%). The cause of morphological error in student’s narrative essays include: (1) lack of writing habit according to the correct language rules, (2) students do not understand about the correct language rules, especially morphological rules, (3) lack of students' understanding of correct morphological rules, so that students are confused about applying theory when practicing writing (4) lack of caution or thoroughness when writing narrative essays.